Sodium-ion battery algal biomass hard carbon negative electrode material and preparation method and application thereof
Patent Information
- Application Number
- CN202611464289.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-20
- Publication Date
- 2026-10-30
AI Technical Summary
但该方案产物为水热炭,目的是获得良好的吸附性能,而无法应用于制备硬碳、以满足钠离子电池负极材料对电化学性能的要求
[0020]本发明还提供一种上述制备方法制备得到的硬碳负极材料。
Smart Images

Figure CN123002822A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of sodium-ion battery anode materials, and relates to a sodium-ion battery algal biomass hard carbon anode material, its preparation method and application, specifically a method for preparing sodium-ion battery algal biomass hard carbon anode material by hydrothermal morphology protection of algae and heteroelement doping. Background Technology
[0002] Sodium-ion batteries, as an emerging electrochemical energy storage technology, are becoming an important supplementary solution to address the bottlenecks in the development of lithium-ion batteries due to their potential in terms of resources, cost, and safety. Sodium-ion batteries exhibit multiple advantages: sodium is extremely abundant and widely distributed in the Earth's crust, significantly reducing raw material costs. Simultaneously, sodium-ion batteries possess better thermal stability, strong resistance to overcharge and over-discharge, and nail penetration tests demonstrate that they are less prone to fire and explosion during short circuits, resulting in higher safety. In terms of performance, sodium-ion batteries have better fast-charging capabilities, a wider operating temperature range, and strong adaptability. Therefore, sodium-ion batteries are considered the future direction of energy storage technology development.
[0003] Hard carbon materials, due to their large interlayer spacing, abundant microporous structure, and excellent cycle stability, are currently the mainstream anode materials for the industrial application of sodium-ion batteries. Biomass hard carbon, with its simple preparation process, wide availability of raw materials, and good sodium storage performance, is considered one of the candidates for hard carbon anode materials in sodium-ion batteries. However, due to the inherent properties of biomass, the structure and elemental composition of its derived hard carbon are difficult to effectively control, limiting further improvements in the electrochemical performance of biomass hard carbon anode materials.
[0004] The use of algae as precursors for hard carbon has attracted considerable attention from researchers. Algae cultivation is simple, less affected by environmental factors, yields high output, and has low cost advantages, leading to its application in various fields. For example, existing patent CN117069103A discloses a method for preparing activated carbon based on solar heating, using large algae or wetland plants such as reeds as raw materials, and reacting them with phosphoric acid in a hydrothermal reactor to prepare activated carbon. In this method, phosphoric acid acts as a chemical activator, used to disrupt the cell wall structure of biomass to form pores. However, the final product of this patent is activated carbon for wastewater treatment, which aims for high specific surface area and abundant pore structure to improve adsorption performance. Furthermore, in this method, phosphoric acid needs to be washed away after the hydrothermal reaction. However, the product of this method is hydrothermal carbon, intended to achieve good adsorption performance, and cannot be used to prepare hard carbon to meet the electrochemical performance requirements of sodium-ion battery anode materials. In addition, the existing patent CN117819519A, a method for preparing hydrothermal carbon material from algae and its application, also discloses a technical solution for preparing hydrothermal carbon from algae. However, its application in improving the geochemical properties of saline-alkali land to increase crop yield is also difficult to apply to the preparation of hard carbon materials.
[0005] Currently, researchers have found that using algal biomass as a carbon precursor to prepare hard carbon materials often faces the following problems: First, the unique spherical morphology of algae is prone to structural collapse and damage during high-temperature carbonization, resulting in the final hard carbon morphology failing to maintain its spherical shape; second, due to the low lignin content of algal biomass, the hard carbon products obtained by direct carbonization contain fewer pseudo-graphite structures, leading to a lower sodium storage capacity; finally, the electrochemical performance of hard carbon prepared from biomass materials is unstable and has not yet met the requirements for large-scale commercial application, necessitating improvement and optimization of existing preparation processes. Based on this, existing patent CN119381448A discloses a sodium-ion hard carbon anode material based on composite raw materials and its preparation method, proposing a technical solution for preparing hard carbon anode materials by using carbonizable algal biomass materials as biomass precursors and combining them with modifiers such as sodium citrate and sodium carboxymethyl cellulose. However, this technical solution relies on the addition of external modifiers to modify algae to achieve structural stability. The resulting hard carbon is mostly an irregular blocky structure with large particles and poor uniformity. Furthermore, the above technical solution produces hard carbon through a two-step carbonization process. The first step, pre-carbonization, involves low-temperature pyrolysis in a high-temperature furnace, a solid-phase process that inevitably makes it difficult to ensure uniform mixing and sufficient reaction between reactants, resulting in poor product uniformity. Moreover, the introduction of modifiers increases process complexity and cost.
[0006] Therefore, this invention is proposed. This invention uses common algae as raw material, alters its structure through hydrothermal processes, and involves elemental doping and the formation of a cross-linked layer on the material surface. The resulting hard carbon anode not only retains its original morphology but also exhibits excellent electrochemical performance, making it highly valuable for commercial applications. Summary of the Invention
[0007] To address the shortcomings of existing technologies, this invention provides a novel, low-cost, and easily industrially feasible method for preparing hard carbon anode materials for sodium-ion batteries using algae as raw material, along with its products and applications. This invention creatively utilizes algae as raw material and employs a hydrothermal pre-carbonization treatment with phosphoric acid to form a cross-linked layer on the algae surface. This cross-linked layer transforms into a carbon skeleton during subsequent high-temperature carbonization, protecting the algae's spherical structure from collapse and damage. Simultaneously, phosphorus from the phosphoric acid is incorporated into the crystal lattice of the hard carbon material, expanding the interlayer spacing and significantly improving the sodium storage performance of the hard carbon anode material. Furthermore, due to the simple cultivation methods of algae, minimal impact from environmental factors, and high yield, this invention offers the significant advantage of extremely low manufacturing costs.
[0008] The technical solution adopted by the present invention to achieve the above-mentioned technical objectives is as follows.
[0009] A method for preparing algal biomass hard carbon anode material for sodium-ion batteries, wherein the method involves hydrothermal and phosphoric acid-controlled pre-carbonization of algae to prepare the sodium-ion battery anode hard carbon material, and the specific preparation method includes the following steps: S1. Algal biomass raw material is mixed with phosphoric acid solution and then subjected to hydrothermal precarbonization treatment to obtain a precarbonized product with a cross-linked layer on the surface. S2. The obtained pre-carbonized product is subjected to high-temperature carbonization treatment under inert gas to obtain hard carbon material.
[0010] By adopting the technical solution of the present invention, the phosphoric acid solution is used to induce the formation of a cross-linked layer on the surface of the algal raw material, and the cross-linked layer is transformed into a carbon skeleton during the high-temperature carbonization process to maintain the spherical structure of the algal biomass raw material. At the same time, the phosphorus element in the phosphoric acid solution is doped into the crystal lattice of the hard carbon material, thereby achieving the successful preparation of the hard carbon material.
[0011] Preferably, the algal biomass raw material mentioned in step S1 is at least one of cyanobacteria, brown algae, Chlamydomonas, Chlorella, Chlorella pyrenoidosa, and Cyclocystis. More preferably, the algal biomass raw material mentioned in step S1 is Chlorella pyrenoidosa.
[0012] Preferably, in step S1, the algal biomass raw material undergoes the following pretreatment before hydrothermal precarbonization: centrifugation and drying of the cultivated algae. Preferably, the centrifugation rate is 2000-8000 rpm, and the centrifugation time is 2-20 min. More preferably, the centrifugation rate is 5000 rpm, and the centrifugation time is 10 min. More preferably, the drying temperature is 40-80℃. Even more preferably, the drying temperature is 50℃.
[0013] Preferably, the concentration of the phosphoric acid solution in step S1 is 0.1-5 mol / L. More preferably, the concentration of the phosphoric acid solution is 0.5-3 mol / L, and even more preferably, it is 2 mol / L.
[0014] Preferably, the mass ratio of algal biomass raw material to phosphoric acid solution in step S1 is 1:2-20. More preferably, the mass ratio is 1:10.
[0015] Preferably, the hydrothermal temperature in step S1 is 180℃-240℃, and the hydrothermal time is 2-24 hours. More preferably, the hydrothermal temperature is 200℃, and the hydrothermal time is 6 hours.
[0016] Preferably, the pre-carbonized product obtained in step S2 is dried before undergoing high-temperature carbonization. More preferably, the drying temperature is 40-80°C, and more preferably 50°C.
[0017] Preferably, the inert atmosphere in step S2 is at least one of nitrogen, helium, and argon.
[0018] Preferably, in step S2, the high-temperature carbonization temperature is 900-1600℃, the holding time is 0.5-4h, and the preferred heating rate is 1-10℃ / min. More preferably, the high-temperature carbonization temperature is 1300℃, the holding time is 2h, and the preferred heating rate is 5℃ / min.
[0019] In the method described in this invention, the key to the hydrothermal pre-carbonization treatment with phosphoric acid lies in the synergistic combination of the concentration of the phosphoric acid solution, the mass ratio of algae to the phosphoric acid solution, the hydrothermal temperature, and the hydrothermal time. Under the combined effect of the above conditions, phosphoric acid can uniformly induce the formation of a cross-linked layer on the surface of algae, rather than merely acting as a pore-forming agent to etch the internal structure of biomass as in the prior art. This difference allows the product of this invention to maintain a complete cross-linked spherical structure after high-temperature carbonization, while the structure of algae without phosphoric acid hydrothermal treatment collapses and breaks down after high-temperature carbonization. Characterization results of scanning electron microscopy and transmission electron microscopy confirm that the hard carbon material prepared by the method of this invention exhibits a cross-linked spherical structure with a continuous carbonized layer and a large number of closed-pore structures on the outer layer, while the control sample without phosphoric acid treatment exhibits a blocky morphology and a discontinuous structure. X-ray diffraction analysis further confirms that the (002) diffraction peak of the hard carbon material prepared by this invention shifts to a smaller angle, indicating that the introduction of phosphorus effectively expands the interlayer spacing of hard carbon, which is beneficial to the insertion and extraction of sodium ions.
[0020] The present invention also provides a hard carbon anode material prepared by the above preparation method.
[0021] The present invention also provides an application of the hard carbon anode material prepared by the above preparation method in the field of sodium-ion batteries.
[0022] The hard carbon material prepared in this invention exhibits excellent electrochemical performance when used as a negative electrode material in sodium-ion batteries. It demonstrates superior sodium storage performance compared to the untreated comparative sample at both low current densities of 0.05 A / g and high current densities of 1 A / g.
[0023] Compared with the prior art, the beneficial effects of this invention are mainly reflected in: First, this invention is the first to discover that hydrothermal treatment with phosphoric acid can form a cross-linked layer on the surface of algae. This cross-linked layer can be transformed into a carbon skeleton during high-temperature carbonization, thereby protecting the spherical structure of the algae from collapse and damage. Furthermore, in this invention, phosphoric acid forms a protective cross-linked layer on the algae surface and is retained within the material for doping. This is significantly different from the conventional effects of phosphoric acid on algal materials, such as its etching properties, in existing technologies.
[0024] Secondly, this invention achieves the dual functions of morphology protection and phosphorus doping simultaneously through hydrothermal pre-carbonization with phosphoric acid. In existing technologies, morphology protection and elemental doping typically require separate processing steps, resulting in complex processes. This invention utilizes a one-step hydrothermal treatment with phosphoric acid to achieve both objectives simultaneously, simplifying the preparation process and reducing production costs.
[0025] Third, this invention uses algae as raw material. Algae cultivation is simple, less affected by environmental factors, and has a large yield. The raw material cost is extremely low, making it suitable for large-scale industrial production.
[0026] Fourth, the hard carbon material prepared by this invention exhibits excellent electrochemical performance. Because the cross-linked layer protects the spherical structure of the algae, the hard carbon material maintains a cross-linked spherical morphology that facilitates the insertion and extraction of sodium ions; simultaneously, the doping of phosphorus expands the interlayer spacing of the hard carbon, further enhancing its sodium storage performance. Attached Figure Description
[0027] Figure 1 The X-ray diffraction (XRD) patterns are of the hard carbon materials prepared in Examples 1 and 2.
[0028] Figure 2 Scanning electron microscope (SEM) images of the hard carbon materials prepared in Examples 1 and 2. It can be seen that the structure of Example 1 is mainly cross-linked spheres, while the structure of Example 2 is mainly blocky.
[0029] Figure 3 These are transmission electron microscope (TEM) images of the hard carbon materials prepared in Examples 1 and 2. It can be seen that the hard carbon material in Example 1 has a continuous graphite structure on the outer layer, while the hard carbon material in Example 2 does not have this continuity.
[0030] Figure 4 Cyclic performance of the hard carbon materials prepared in Examples 1 and 2 at a current density of 0.05 A / g.
[0031] Figure 5 Cyclic performance of the hard carbon materials prepared in Examples 1 and 2 at a current density of 1 A / g. Detailed Implementation
[0032] To better clarify and understand the purpose, process scheme, and advantages of the present invention, the technical solution and implementation methods of the present invention will be further described clearly, completely, and in detail below through specific embodiments and in conjunction with the accompanying drawings. It should be understood that the embodiments described in this invention are implemented under the premise of the technical solution of the present invention, providing detailed implementation methods and specific operating processes, but are only some embodiments of the present invention, not all embodiments. The specific implementation methods described are limited to illustrating and explaining the present invention and do not limit the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Various improvements and changes can be made to the specific implementation methods of the present invention without departing from the scope or spirit of the present invention, which is obvious to those skilled in the art. Other implementation methods obtained from the present invention specification are obvious to those skilled in the art. The present invention specification and embodiments are merely exemplary.
[0033] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. It should be noted that any aspects of this invention not described in detail are conventional practices in the art and are not the focus of this invention. The terms "comprising," "including," "having," "containing," etc., as used herein are open-ended terms, meaning they include but are not limited to. It should be noted that any aspects of this invention not described in detail are conventional practices in the art and are not the focus of this invention.
[0034] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0035] Unless otherwise specified, the experimental methods and conditions used in the embodiments of this invention are conventional methods and conditions. The materials, reagents, instruments, and equipment used in the embodiments, unless otherwise specified, are all conventional substances or equipment known to those skilled in the art and can be obtained commercially or prepared by conventional methods. The reaction conditions described in the invention's content can all achieve the stated reactions and obtain the desired products. Due to space limitations, some embodiments are listed below to further illustrate the advantages of the technical solution of this invention.
[0036] The following are relevant information about the raw materials used in specific embodiments of the present invention, but are not limited to the specific information described below. Any substance or instrument with equivalent efficacy can achieve the technical solution and technical effect described in the present invention and falls within the protection scope of the present invention: Raw materials: Algal biomass such as cyanobacteria, brown algae, Chlamydomonas, Chlorella, Chlorella pyrenoidosa, Chlorella proteoglycans, and Cyclostome, all of which were obtained commercially and routinely propagated in the laboratory.
[0037] Example 1: Chlorella proteoglycans cultured in water were centrifuged at 5000 r / min for 10 min, and then the collected Chlorella proteoglycans were dried at 50 °C. The dried Chlorella proteoglycans were added to a 2 mol / L phosphate solution at a mass ratio of algae to solution of 1:10, and pre-carbonized hydrothermally at 200 °C for 6 hours. The pre-carbonized material was collected, dried at 50 °C, and then heated to 1300 °C at a heating rate of 5 °C / min under argon atmosphere and held at that temperature for 2 hours to obtain hard carbon material.
[0038] Using N-methylpyrrolidone (NMP) as a solvent, conductive carbon black (super-P), polyvinylidene fluoride (PVDF), and active material (the aforementioned hard carbon material) are mixed in a mass percentage ratio of 10:10:80 to form a slurry, which is then uniformly coated onto aluminum foil. The coating amount is typically 2 mg / cm³. -2 After drying at 120℃ under vacuum for 12 hours, the electrode sheets were cut and set aside. Then, the electrode sheets were assembled into a sodium-ion half-cell in an argon-atmosphere glove box. First, the positive electrode shell, the electrode sheets, the separator, the sodium sheet, the stainless steel gasket, the spring sheet, and the negative electrode shell were stacked sequentially, and an appropriate electrolyte was added before sealing. The battery shell used was a CR2032 type, the separator was made of glass fiber (Waterman), and the electrolyte was 1 mol NaPF6-DME.
[0039] Example 2: Chlorella proteoglycans cultured in water were centrifuged at 5000 r / min for 10 min, and then the collected Chlorella proteoglycans were dried at 50 °C. The dried Chlorella proteoglycans were added to a 0 mol / L phosphoric acid solution at a mass ratio of algae to solution of 1:10, and pre-carbonized hydrothermally at 200 °C for 6 hours. The pre-carbonized material was collected, dried, and then heated to 1300 °C at a heating rate of 5 °C / min under argon atmosphere and held at that temperature for 2 hours to obtain hard carbon material. The battery assembly method was the same as in Example 1.
[0040] Analysis of Example 1 and Example 2 Figure 1 The X-ray diffraction (XRD) patterns are shown for the hard carbon materials prepared in Examples 1 and 2. (See attached images.) Figure 1 As can be seen, after the preparation strategy described in this invention, the samples of Examples 1 and 2 show obvious diffraction peaks of hard carbon. Among them, the (002) peak of hard carbon in Example 1 shifted and the angle decreased, indicating that the introduction of phosphorus expanded the interlayer spacing of hard carbon.
[0041] Figure 2 Scanning electron microscope (SEM) images of the hard carbon materials prepared in Examples 1 and 2. Figure 3 Transmission electron microscope (TEM) images of the hard carbon materials prepared in Examples 1 and 2. (Attached) Figure 2 , 3In Example 1, the scanning electron microscope (SEM) morphology showed a cross-linked spherical structure. This indicates that Example 1, with its phosphoric acid hydrothermal treatment, was able to form a cross-linked structure on the surface of *Chlorella vulgaris*, and successfully generated a complete and continuous graphite carbonization layer after high-temperature carbonization, which was also observed by transmission electron microscopy (TEM), and contained a large number of closed-pore structures. In contrast, Example 2, lacking the participation of phosphoric acid in the hydrothermal treatment, failed to form a continuous cross-linked layer. The structure collapsed and broke down after subsequent high-temperature carbonization, thus showing a non-uniformly dispersed, discontinuous, but multi-layered graphite structure and a small number of closed-pore structures in TEM, while SEM showed a blocky morphology. The morphology of Example 1 is more conducive to the insertion and extraction of sodium ions during the charge and discharge process.
[0042] Figure 4 Cyclic performance of the hard carbon materials prepared in Examples 1 and 2 at a current density of 0.05 A / g. Figure 5 The cycling performance of the hard carbon materials prepared in Examples 1 and 2 at a current density of 1 A / g is shown in the appendix. Figure 4 , 5 As can be seen, regardless of the small current (0.05A g) -1 ) or high current (1A g) -1 Example 1 showed improved sodium storage performance, indicating that the addition of phosphoric acid can improve the sodium ion storage performance of the material. Implementing the technical solution of this invention can effectively improve the microstructure of hard carbon and the overall performance of sodium-ion battery anode materials.
[0043] Example 3: The Chlorella proteoglycans cultured in water were centrifuged at 3000 r / min for 20 min, and then the collected Chlorella proteoglycans were dried at 50 °C. The dried Chlorella proteoglycans were added to a 0.5 mol / L phosphate solution with a mass ratio of algae to solution of 1:10, and pre-carbonized hydrothermally at 200 °C for 6 hours. The pre-carbonized material was collected, dried, and heated to 1300 °C at a heating rate of 5 °C / min under argon atmosphere, and held at that temperature for 2 hours.
[0044] Example 4: The Chlorella proteoglycans cultured in water were centrifuged at 5000 r / min for 10 min, and then the collected Chlorella proteoglycans were dried at 50 °C. The dried Chlorella proteoglycans were added to a phosphate solution containing 2 mol / L, with a mass ratio of algae to solution of 1:10, and pre-carbonized hydrothermally at 200 °C for 12 hours. The pre-carbonized material was collected, dried, and heated to 1500 °C at a heating rate of 10 °C / min under argon atmosphere, and held at that temperature for 2 hours.
[0045] Example 5: The cyanobacteria cultured in water were centrifuged at 8000 r / min for 10 min, and then the collected Chlorella proteoglycans were dried at 50 °C. The dried Chlorella proteoglycans were added to a phosphate solution containing 1 mol / L, with a mass ratio of algae to solution of 1:5, and pre-carbonized hydrothermally at 220 °C for 12 hours. The pre-carbonized material was collected, dried, and heated to 1500 °C at a heating rate of 10 °C / min under argon atmosphere, and held at that temperature for 1 hour.
[0046] Example 6: The Chlorella proteoglycans cultured in water were centrifuged at 8000 r / min for 10 min, and then the collected Chlorella proteoglycans were dried at 50 °C. The dried Chlorella proteoglycans were added to a phosphate solution containing 1 mol / L, with a mass ratio of algae to solution of 1:5, and pre-carbonized hydrothermally at 220 °C for 12 hours. The pre-carbonized material was collected, dried, and heated to 1500 °C at a heating rate of 10 °C / min under nitrogen atmosphere and held at that temperature for 1 hour.
[0047] Example 7: The Chlorella cultured in water was centrifuged at 5000 r / min for 10 min, and then the collected Chlorella proteoglycans were dried at 50 °C. The dried Chlorella proteoglycans were added to a phosphate solution containing 3 mol / L, with a mass ratio of algae to solution of 1:5, and pre-carbonized hydrothermally at 180 °C for 12 hours. The pre-carbonized material was collected, dried, and heated to 1500 °C at a heating rate of 5 °C / min under argon atmosphere, and held at that temperature for 2 hours.
[0048] Example 8: Brown algae cultured in water were centrifuged at 5000 r / min for 10 min, and the collected Chlorella proteoglycans were dried at 50 °C. The dried Chlorella proteoglycans were added to a phosphate solution containing 3 mol / L, with a mass ratio of algae to solution of 1:10, and pre-carbonized hydrothermally at 200 °C for 12 hours. The pre-carbonized material was collected, dried, and heated to 1500 °C at a heating rate of 5 °C / min under argon atmosphere, and held at that temperature for 2 hours.
[0049] Example 9: The Chlorella proteoglycans cultured in water were centrifuged at 5000 r / min for 10 min, and then the collected Chlorella proteoglycans were dried at 50 °C. The dried Chlorella proteoglycans were added to a 0.5 mol / L phosphate solution with a mass ratio of algae to solution of 1:10, and pre-carbonized hydrothermally at 200 °C for 12 hours. The pre-carbonized material was collected, dried, and heated to 1100 °C at a heating rate of 5 °C / min under argon atmosphere, and held at that temperature for 2 hours.
[0050] Example 10: The Chlorella proteoglycans cultured in water were centrifuged at 5000 r / min for 10 min, and then the collected Chlorella proteoglycans were dried at 50 °C. The dried Chlorella proteoglycans were added to a phosphate solution containing 2 mol / L, with a mass ratio of algae to solution of 1:10, and pre-carbonized hydrothermally at 200 °C for 12 hours. The pre-carbonized material was collected, dried, and heated to 1100 °C at a heating rate of 5 °C / min under helium atmosphere, and held at that temperature for 2 hours.
[0051] Application examples Referring to the battery fabrication method in Example 1, corresponding batteries were prepared using the materials from each example, and their electrochemical performance was tested. The test results are shown in Table 1 below.
[0052] Table 1 Summary of Electrochemical Performance of Each Example
[0053] This invention innovatively employs a phosphoric acid hydrothermal pre-carbonization treatment of algal raw materials. Under phosphoric acid hydrothermal conditions, the algal material forms a continuous and stable cross-linked layer. This cross-linked layer is formed after low-temperature hydrothermal treatment and subsequently transforms into a continuous graphite layer at high temperatures. This stable cross-linked layer is crucial for the algal material to maintain its original morphology at high temperatures. Therefore, the hard carbon obtained by this invention has a spherical structure, small particle size, and a generally consistent product morphology. In contrast, algal material without added phosphoric acid cannot form a sufficiently large, continuous, and uniform cross-linked layer. During subsequent high-temperature carbonization, it transforms into a non-uniformly dispersed and discontinuous graphite structure, failing to maintain the original spherical morphology of the algal material.
[0054] Meanwhile, compared to existing technologies that achieve phosphorus doping primarily through methods such as ball milling of hard carbon materials with phosphorus, which can easily damage the spherical structure of algae and is mostly mechanical doping, this invention achieves phosphorus doping by introducing phosphorus into the carbon framework of hard carbon, rather than through simple mechanical mixing. Furthermore, the introduction of phosphorus in this invention aims to widen the interlayer spacing and increase defects in the carbon layers, thereby creating more space for sodium ion storage. This sodium storage mechanism is significantly different from existing phosphorus doping schemes. Moreover, this invention achieves superior electrochemical performance, greatly increasing the sodium storage capacity of the material through the introduction of phosphoric acid, and exhibiting excellent cycle stability.
[0055] Furthermore, this invention uses a hydrothermal method for pre-carbonization, which has a lower temperature and better safety. The use of liquid-solid mixing for hydrothermal processing not only ensures that the reactants are mixed evenly, but also makes the product more uniform.
[0056] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the present invention in any way. Other variations and modifications are possible without departing from the technical solutions described in the claims.
Claims
1. A method for preparing algae biomass hard carbon anode material for sodium-ion batteries, characterized in that, Includes the following steps: S1. Algal biomass raw material is mixed with phosphoric acid solution and then subjected to hydrothermal precarbonization treatment to obtain a precarbonized product with a cross-linked layer on the surface. S2. The obtained pre-carbonized product is subjected to high-temperature carbonization treatment under inert gas to obtain hard carbon material.
2. The preparation method according to claim 1, characterized in that, The algae mentioned in step S1 are selected from at least one of cyanobacteria, brown algae, Chlamydomonas, Chlorella, Chlorella, Chlorella pyrenoidosa, and Cyclostome.
3. The preparation method according to claim 1, characterized in that, In step S1, before undergoing hydrothermal precarbonization, the algae biomass raw material undergoes the following pretreatment: centrifugation and drying of the cultured algae.
4. The preparation method according to claim 3, characterized in that, Centrifugation rate is 2000-8000 rpm, centrifugation time is 2-20 min; And / or, the drying temperature is 40-80℃.
5. The preparation method according to claim 1, characterized in that, In step S1, the concentration of the phosphoric acid solution is 0.1-5 mol / L, and the mass ratio of algal biomass raw material to phosphoric acid solution is 1:2-20. And / or, the hydrothermal temperature is 180℃-240℃, and the hydrothermal time is 2-24h.
6. The preparation method according to claim 5, characterized in that, In step S1, the concentration of the phosphoric acid solution is 2 mol / L, and the mass ratio of algal biomass raw material to phosphoric acid solution is 1:
10. And / or, the hydrothermal temperature is 200℃ and the hydrothermal time is 6h.
7. The preparation method according to claim 1, characterized in that, In step S2, the high-temperature carbonization temperature is 900-1600℃, and the holding time is 0.5-4h.
8. The preparation method according to claim 7, characterized in that, In step S2, the high-temperature carbonization temperature is 1300℃ and the holding time is 2 hours.
9. A hard carbon anode material prepared by the preparation method according to any one of claims 1-8.
10. The application of a hard carbon anode material prepared by the preparation method according to any one of claims 1-8 in the field of sodium-ion batteries.
Citation Information
Patent Citations
Sodium ion hard carbon negative electrode material based on composite raw material and preparation method of sodium ion hard carbon negative electrode material
CN119381448A
